"Reverse" pyridyl cryptands as hosts for viologens. Issue 3 (10th July 2018) - Pederson, Adam M.‐P.; Price, Terry L.; Schoonover, Daniel V.; Slebodnick, Carla; Gibson, Harry W.
Abstract: Two new cryptands, 2 and4, were prepared from bis( m ‐phenylene)‐32‐crown‐10 (BMP32) 5, 5'‐diacid chloride and dibenzo‐30‐crown‐10 (DB30) 4, 4'‐diacid chloride, respectively, by reaction with pyridine‐2, 6‐dimethanol. The resultant cryptands2 and4 have the ester moieties reversed from the previously reported isomers, 1 and3 . These "reverse" cryptands display lower association constants with viologen derivatives than the original cryptands; this is rationalized by the conjugation of the ester moieties with the aromatic rings, which reduces their electron‐donating properties and offsets the increased basicity of the pyridyl nitrogen atoms. The crystal structure of the BMP32‐based cryptand2 indeed confirms the coplanarity of the ester and aromatic moieties and indicates that, as a result, the available cavity is quite small and that the pyridyl nitrogen atom points away from the cavity.